MicroRNA-424(322) as a new marker of disease progression in pulmonary arterial hypertension and its role in right ventricular hypertrophy by targeting SMURF1. (12th September 2017) - Baptista, Rui; Marques, Carla; Catarino, Steve; Enguita, Francisco J; Costa, Marina C; Matafome, Paulo; Zuzarte, Mónica; Castro, Graça; Reis, Abílio; Monteiro, Pedro; Pêgo, Mariano; Pereira, Paulo; et al.
Abstract: Aims: MicroRNAs (miRNAs) have been implicated in the pathogenesis of pulmonary hypertension (PH), a multifactorial and progressive condition associated with an increased afterload of the right ventricle leading to heart failure and death. The main aim of this study was to correlate the levels of miR-424(322) with the severity and prognosis of PH and with right ventricle hypertrophy progression. Additionally, we intended to evaluate the mechanisms and signalling pathways whereby miR-424(322) secreted by pulmonary arterial endothelial cells (PAECs) impacts cardiomyocytes. Methods and results: Using quantitative real-time PCR, we showed that the levels of circulating miR-424(322) are higher in PH patients when compared with healthy subjects. Moreover, we found that miR-424(322) levels correlated with more severe symptoms and haemodynamics. In the subgroup of Eisenmenger syndrome patients, miR-424(322) displayed independent prognostic value. Furthermore, we demonstrated that miR-424(322) targets SMURF1, through which it sustains bone morphogenetic protein receptor 2 signalling. Moreover, we showed that hypoxia induces the secretion of miR-424(322) by PAECs, which after being taken up by cardiomyocytes leads to down-regulation of SMURF1. In the monocrotaline rat model of PH, we found an association between circulating miR-424(322) levels and the stage of right ventricle hypertrophy, as well as an inverse correlation between miR-424(322) and SMURF1 levels in the hypertrophied right ventricle. Conclusions: This study shows that miR-424(322) has diagnostic and prognostic value in PH patients, correlating with markers of disease severity. Additionally, miR-424(322) can target proteins with a direct effect on heart function, suggesting that this miRNA can act as a messenger linking pulmonary vascular disease and right ventricle hypertrophy.